Kinetics and kinetics-free simulation of oil palm biomass waste torrefaction - Yong, Yung Sheng; Ruwaida, Abdul Rasid; Mazni, Ismail (UKM Press, 2026)
Torrefaction is a thermochemical process in which oil palm waste is heated to generate high calorific value, energy density, and a storable green fuel. This work aims to generate a computational model that can simulate the torrefaction process for the empty fruit bunch (EFB) and evaluate the model outcomes with and without the reaction kinetics. It is shown that the solid carbon mass fraction reduced steadily against temperature, while other liquids and gases increased as more volatile matter was released due to the decomposition of hemicellulose in the biomass. The heat duty decreased when the reactor’s temperature increased, which is due to the decreased activation energy required for the decomposition reaction, as the increase of extractives, including the condensable and non-condensable products, acted as the catalyst for the decomposition to occur. The kinetic involvement in the model is proven to increase the accuracy of the product distribution as it has a higher similarity of the trend of distribution towards the literature compared to non-kinetics, specifically 86.41%, 76.05% and 89.23% error reduction for solids, liquids and gases, respectively. The heat duty of the kinetic model is more realistic due to the involvement of kinetic parameters in the study. In conclusion, applying computational and kinetic modelling can simulate the torrefaction process and will be further introduced to the industry